2007
DOI: 10.1002/ptr.2072
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical and therapeutic Potentials of essential oils and their individual volatile constituents: a review

Abstract: Essential oils and their volatile constituents are used widely to prevent and treat human disease. The possible role and mode of action of these natural products is discussed with regard to the prevention and treatment of cancer, cardiovascular diseases including atherosclerosis and thrombosis, as well as their bioactivity as antibacterial, antiviral, antioxidants and antidiabetic agents. Their application as natural skin penetration enhancers for transdermal drug delivery and the therapeutic properties of ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
716
0
41

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,095 publications
(763 citation statements)
references
References 232 publications
(197 reference statements)
6
716
0
41
Order By: Relevance
“…Aromatherapy is a form of complementary or alternative medicine that uses essential oils and other scented plant compounds for therapeutic purposes, affecting a person's mood or health (Kiecolt-Glaser et al, 2008). Thus, essential oils as a rich source of flavor molecules are used widely to prevent and treat human diseases (Edris, 2007). The sesquiterpene artemisinin, derived from Artemisia annua, has attracted special attention due to its anti-malarial activity (Kindermans et al, 2007).…”
Section: Possible Uses Of Flavor Moleculesmentioning
confidence: 99%
“…Aromatherapy is a form of complementary or alternative medicine that uses essential oils and other scented plant compounds for therapeutic purposes, affecting a person's mood or health (Kiecolt-Glaser et al, 2008). Thus, essential oils as a rich source of flavor molecules are used widely to prevent and treat human diseases (Edris, 2007). The sesquiterpene artemisinin, derived from Artemisia annua, has attracted special attention due to its anti-malarial activity (Kindermans et al, 2007).…”
Section: Possible Uses Of Flavor Moleculesmentioning
confidence: 99%
“…These volatile substances are commonly found in aromatic plants and their therapeutic potentials have been lately evaluated (Kris-Etherton et al, 2002;Edris, 2007;Paduch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…properties of essential oils in the cardiovascular system as antithrombotic, antiplatelet, endothelial protective, vasorelaxant and hypotensive activities (Lahlou et al, 2005;Edris, 2007). Recent reports have showed that cardiovascular effects of essential oils also occur in humans as improvement in coronary flow (Shiina et al, 2008) and hypotensive and bradycardic effects (Dayawansa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…7) Some essential oil components reportedly have anti-inflammatory activity. 8) The advantage of these components in antiinflammatory therapy is their low or negligible toxicity. Therefore, such components are useful in the long-term chemoprevention and chemotherapy of inflammation.…”
mentioning
confidence: 99%